Demonstration Methods in Primary Schools: A Study of Academic Achievement in Physical and Health Education - Nkwocha, Francis Kehinde; Owolabi, Wasiu (Papanda Publisher, 2023)
This research aimed to investigate how the demonstration method influences the academic performance of primary school students in physical and health education in Kwara State, Nigeria. The study followed a quasi-experimental design, involving 79 pupils from two public primary schools. The research utilized the 'Physical and Health Education Achievement Test (PHEAT)' as the assessment tool, which was carefully validated and tested for its reliability, showing a reliability index of 0.76 using the test-retest method. Two hypotheses were formulated and examined using Analysis of Covariance (ANCOVA). The results of the study revealed a significant positive impact of the demonstration method on pupils' academic achievement in Physical and Health Education. However, when considering gender as a factor, the interaction between treatment and gender did not show a significant effect on pupils' academic achievement in the same subject. In conclusion, the findings suggest that using the demonstration method can enhance the academic achievement of primary school pupils in physical and health education, irrespective of their gender. Based on these results, it is recommended that teachers receive training in utilizing the demonstration method while teaching Physical and Health Education.